Disasters and Resilient City. Issue 3 (1st February 2022) - Potapova, E; Kruchina, E; Barkhatova, O; Makarov, A
Abstract: About 200 million people suffer annually from natural disasters. The economic damage of these events amounts to billions of dollars. In circumstances where more than 50% of the world's population lives in cities, naturally arises challenge related to implementation of new methods and means aimed at enhancing the capacity of authorities to ensure the safety of human capital, economic values and natural resources. Resilience of cities, regarded as the ability to keep effective functioning during and after natural disasters, is determined by the many criteria. The most important of it is the correct organizational and planning structure of the settlement that meets the Sustainable Development Goals. The presence of a completed scientifically grounded and rational greening of the settlement system will allow for the main range of ecosystem services - from global, sanitary and hygienic and medico-social to scientific, educational, cultural and aesthetic. There are 6 main associated with the objects of greening and plantings subgroups of city resilience criteria. 8 main directions of work of the governing bodies are proposed to achieve the goals of the development of settlements in accordance with the principles of enhancing the viability. 8 main directions of governing bodies work are proposed to achieve the goals of the development of settlements in accordance with the principles of enhancing the city resilience.